Permainan Edukasi Puzzle Math Untuk Menstimulasi Motorik Siswa - Rahmadani, Elfira; Supiatman, Lis; Fazariah, Nur Aisiyah; Wulandari, Putri; Aprilia, Cahyani; Lubis, M Rifaldi (STMIK Royal, 2024)
This service examines the necessity and pertinence of adopting a pedagogical approach that incorporates educational game components in order to promote motor development and enhance student engagement in the learning process. On November 18, 2023, this service activity was conducted at UPTD. SD Negeri 014672 Tanjung Alam. This activity is structured into three distinct phases during its execution: preparation, implementation, and practice. Based on empirical findings, engaging in direct interaction with mathematical puzzles has been found to enhance hand-motor coordination, finger dexterity, and precision control during object manipulation. Ninety-five percent of students were extremely interested in this educational game; eighty-five percent felt that math puzzle games improved their fine motor skills (hand and finger movements); and ninety-two percent intend to continue playing math puzzles on other materials in the future, according to the results of the questionnaire assessing the experience of playing with math puzzles. Students' fine motor skills improved significantly as a result of the implementation of this game, it was concluded.